Elements of Vorticity Aerodynamics - Wu, James C. (Springer Tracts in Mechanical Engineering,, 2018)
This book opens with a discussion of the vorticity-dynamic formulation of the low Mach number viscous flow problem. It examines the physical aspects of the velocity and the vorticity fields, their instantaneous relationship, and the transport of vorticity in viscous fluids for steady and unsteady flows. Subsequently, using classical analyses it explores the mathematical aspects of vorticity dynamics and issues of initial and boundary conditions for the viscous flow problem. It also includes the evolution of the vorticity field which surrounds and trails behind airfoils and wings, generalizations of Helmholtz' vortex theorems and the Biot-Savart Law. The book introduces a theorem that relates the aerodynamic force to the vorticity moment and reviews the applications of the theorem. Further, it presents interpretations of the Kutta-Joukowski theorem and Prandtl's lifting line theory for vorticity dynamics and discusses wake integral methods. The virtual-mass effect is shown to be the seminal event in unsteady aerodynamics and a simple approach for evaluating virtual-mass forces on the basis of vorticity dynamics is presented. The book presents a modern viewpoint on vorticity dynamics as the framework for understanding and establishing the fundamental principles of viscous and unsteady aerodynamics. It is intended for graduate-level students of classical aerodynamics and researchers exploring the frontiers of fully unsteady and non-streamlined aerodynamics.